2011
DOI: 10.1007/s00221-011-2555-9
|View full text |Cite
|
Sign up to set email alerts
|

Internal models of self-motion: computations that suppress vestibular reafference in early vestibular processing

Abstract: In everyday life, vestibular sensors are activated by both self-generated and externally applied head movements. The ability to distinguish inputs that are a consequence of our own actions (i.e., active motion) from those that result from changes in the external world (i.e., passive or unexpected motion) is essential for perceptual stability and accurate motor control. Recent work has made progress toward understanding how the brain distinguishes between these two kinds of sensory inputs. We have performed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 64 publications
4
58
0
Order By: Relevance
“…In addition, the Koos IV VS patients alone had significantly lower performances for the C3 ES and C4 ES conditions than the control group. This result suggests that VS compression of the central nervous structures might not only alter vestibular function, but also sensory integrative processes (Kammermeier et al, 2009;Cullen et al, 2011;Cullen, 2012). Our results for the Koos IV stage agree with a previous study that found higher central disturbances, such as a higher occurrence of balance disorders, higher auditory brainstem response thresholds, and lower occurrence of tinnitus with similar hearing loss, compared to the lower Koos stages (Tringali et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the Koos IV VS patients alone had significantly lower performances for the C3 ES and C4 ES conditions than the control group. This result suggests that VS compression of the central nervous structures might not only alter vestibular function, but also sensory integrative processes (Kammermeier et al, 2009;Cullen et al, 2011;Cullen, 2012). Our results for the Koos IV stage agree with a previous study that found higher central disturbances, such as a higher occurrence of balance disorders, higher auditory brainstem response thresholds, and lower occurrence of tinnitus with similar hearing loss, compared to the lower Koos stages (Tringali et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…If there were a significant and synergistic passive VOR component, then that component would have been suppressed by GVS and we should have detected a difference in the compensatory eye movements that occurred during GVS and control epochs of self-generated head movement. Thus this finding supports the idea that an efference copy of the motor command to move the head is used to cancel the sensory consequence (reafference) of the planned head movement (Cullen et al 2011;Sadeghi et al 2010;Shanidze et al 2010b;von Holst and Mittelstaedt 1950). If the active head movement occurs as planned, then the vestibular nerve signal is effectively nullified centrally by the efference copy and would produce no VOR-related eye movement.…”
Section: Ocular Compensation During Self-generated Head Movementssupporting
confidence: 74%
“…We are not able to tease apart separate effects of these various head-on-body cues. Some prior studies have attempted to dissociate proprioceptive and efference copy cues, either by rotating the head passively on the body, leading to proprioceptive but not efference copy signals, or by blocking active head movements, leading to efference copy but no proprioception (Crowell et al 1998;Cullen et al 2011;Nakamura and Bronstein 1995). These studies conclude that both signals play a significant role.…”
Section: Relative Contribution Of Vestibular and Proprioceptive/effementioning
confidence: 95%